FMEA and its application in the SPC - Bebr, Lukáš; Bícová, Kateřina (Advances in Mechanical and Materials Engineering, 2017)
In today’s industry, particularly in the automotive industry, the Failure Mode and Effects Analysis (FMEA) method is a frequently used tool. FMEA is one of the tools which help to identify the causes of process variability and thereby the possibilities of defect occurrence in the evaluated design including the evaluation of their relevant risks. This paper describes the application of the FMEA method to the manufacturing process, with the aim to identify the main causes of process variability, which can affect the resulting product. Further the article introduces other types of FMEA methods based on the basic model, however tailored for specific use in various areas. Finally, the measures, actions and recommendations for correct implementation of the FMEA process are mentioned.